Activation of oil palm empty bunches with hydrochloride acid & phosphoric acid and characterization based SNI No. 06-3730-1995 - Irna Diah Mumpuni; Mamay Maslahat; Devy Susanty (Universitas Nusa Bangsa, 2021)
Activated carbon is a solid product resulting from carbonization and activation of lignocellulosic biomass by several methods and activators. Each activator can produce different characteristics of activated carbon. The activated carbon of Oil Palm Empty Fruit Bunches (OPEFB) is processed from Empty Fruit Bunches (EFB) waste, which is quite abundant in Indonesia. The purpose of this study was to determine the characteristics of OPEFB carbon that had been chemically activated using hydrochloric acid (HCl) and phosphoric acid (H3PO4) based on the Indonesian National Standard (SNI) No. 06 - 3730 - 1995. The research method consisted of the process of carbonization of OPEFB using a pyrolysis device at 400oC for 6 hours; activation of carbon with activator HCl and H3PO4 at various activator concentrations; characterization of activated carbon on the parameters of moisture content, ash content, absorption of iodine, and absorption of methylene blue. The results showed that the 0.5000 M HCl was the best activator that produced the quality of OPEFB activated carbon according to SNI 06 - 3730 - 1995 on parameters of moisture content, ash content and absorption of iodine.Keywords: Activated Carbon, Iodine Absorption, Oil Palm Empty Fruit BunchesABSTRAKAktivasi karbon tandan kosong kelapa sawit dengan asam klorida dan asam fosfat serta uji karakterisasi berdasarkan SNI No. 06–3730–1995Karbon aktif merupakan produk padatan yang dihasilkan dari karbonisasi dan aktivasi biomassa lignoselulosa dengan beberapa metode dan aktivator. Masing-masing aktivator dapat menghasilkan karakteristik karbon aktif yang berbeda. Karbon aktif Tandan Kosong Kelapa Sawit (TKKS) diolah dari limbah TKKS yang keberadaannya cukup melimpah di Indonesia. Tujuan penelitian ini adalah mengetahui karakteristik karbon TKKS yang telah diaktivasi secara kimia menggunakan aktivator asam klorida (HCl) dan asam fosfat (H3PO4) berdasarkan Standar Nasional Indonesia (SNI) No. 06 – 3730 – 1995. Metode penelitian terdiri atas proses karbonisasi TKKS menggunakan alat pirolisis pada suhu 400 ℃ selama 6 jam; aktivasi karbon dengan aktivator HCl dan H3PO4 pada berbagai konsentrasi aktivator; serta karakterisasi karbon aktif pada parameter kadar air dan abu, daya jerap terhadap iod serta daya jerap terhadap biru metilen. Hasil penelitian menunjukkan bahwa HCl 0,5 M merupakan aktivator terbaik dan karbon aktif yang dihasilkan memiliki karakteristik yang sesuai dengan SNI 06 – 3730 – 1995 pada parameter kadar air dan abu serta daya jerap terhadap iod.Kata kunci: Daya Jerap Iod, Karbon Aktif, Tandan Kosong Kelapa Sawit